2018
DOI: 10.1136/bmjgh-2017-000573
|View full text |Cite
|
Sign up to set email alerts
|

Violence against children in South Africa: the cost of inaction to society and the economy

Abstract: Despite the extent and magnitude of violence against children in South Africa, political and financial investments to prevent violence against children remain low. A recent costing study investigating the social burden and economic impact of violence against children in South Africa found notable reductions to mental and physical health outcomes in the population if children were prevented from experiencing violence, neglect and witnessing family violence. The results showed, among others, that drug abuse in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…However, the authors were not able to ascertain at the time of the writing the reasons why this may be so in the South African context. The literature on violence against children in South Africa has repeatedly shown that African children bear the brunt of violent acts and abuse committed against them whether by family, community members, strangers or their peers (Hsiao et al 2018;Mathews & Benevuti 2014;Optimus Study 2016;Richter et al 2018). Below is a breakdown of the racial distribution of children reported to Missing Children SA: Surprisingly, 'white' or Caucasian children make up the majority of children reported missing.…”
Section: The Scope Nature and Extent Of Missing Children In South Afmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the authors were not able to ascertain at the time of the writing the reasons why this may be so in the South African context. The literature on violence against children in South Africa has repeatedly shown that African children bear the brunt of violent acts and abuse committed against them whether by family, community members, strangers or their peers (Hsiao et al 2018;Mathews & Benevuti 2014;Optimus Study 2016;Richter et al 2018). Below is a breakdown of the racial distribution of children reported to Missing Children SA: Surprisingly, 'white' or Caucasian children make up the majority of children reported missing.…”
Section: The Scope Nature and Extent Of Missing Children In South Afmentioning
confidence: 99%
“…The Optimus Study (2016) found that one in five children (19.8%) experienced sexual abuse, one in three (34.4%) experienced physical abuse, one in six (16.1%) reported experiencing emotional abuse, one in eight (12.2%) reported being neglected and one in six (16.9%) reported witnessing violence. In terms of physical and sexual abuse, South African children experience more violence compared to the global average (Hsiao et al 2018;Optimus Study, 2016). In a separate study, Mathews, Govender and Lamb et al (2016) found children were at highest risk of violence:…”
Section: Democratisation and The Legacy Of Violence In Post-apartheidmentioning
confidence: 99%
See 3 more Smart Citations